Response surface methodology as an approach for optimization of alpha amylase production by using bacterial consortium under submerged fermentation - Abdullah R.; Ahmad S.; Nisar K. (Kuwait Journal of Science)
The present study aims to isolate amylolytic bacteria and later the formation of a bacterial consortium for alpha-amylase production. The potent amylolytic strains in a selected consortium were identified as B. subtilis and B. licheniformis on the basis of 16S rRNA sequencing. Initially cultural conditions for alpha amylase were optimized in Plackett–Burman design, followed by the central composite design. Analysis of Variance (ANOVA) of the optimization study indicated pH 7, 0.05 %CaCl2 and 24 h incubation time were the significant variables that mainly effect the alpha amylase production. After the process of statistical optimization, the enzyme was then partially purified by means of ammonium sulfate precipitation at a 60% saturation level, resulting in a 2-fold purification with 1.4 U/mg specific activity. Enzyme kinetics studies showed that the maximum velocity of the reaction (Vmax) and Michaelis constant (Km) were 47.4 mg/ml and 13.2 mM, respectively. Current results suggest the newly isolated bacterial consortium could be considered as a promising candidate for industrial applications. © 2024 The Authors